Scattering and Absorption of Waves by Flat Material Strips Analyzed Using Generalized Boundary Conditions and Nystrom-Type Algorithm - Shapoval, O. V.; Sauleau, R.; Nosich, A. I. (IEEE transactions on antennas and propagation, 2011)
The scattering of the H- and E-polarized plane waves by a thin flat homogeneous magneto-dielectric strip is considered. Assuming the strip to be thinner than the wavelength, we shrink its cross-section to the median line where the generalized boundary conditions are imposed. The numerical solution is built on two singular integral equations discretized using Nystrom-type numerical algorithm. The obtained results demonstrate fast convergence and good agreement with data known for the limiting values of the strip parameters. This opens a way to the accurate numerical analysis of various striplike configurations simulating natural objects and electromagnetic circuit components, both in traditional microwave applications and nanophotonics.